2015
DOI: 10.1186/s12936-015-0987-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a recent malaria outbreak in the autonomous indigenous region of Guna Yala, Panama

Abstract: BackgroundThis study aims to describe the epidemiological and entomological factors associated with a recent malaria outbreak that occurred in 2012 in a socially marginalized population from Guna Yala Comarca in Panama.MethodsA descriptive and observational study was conducted by analysing demographic and epidemiological data from all malaria cases registered during 2012 in the Comarca Guna Yala, Panama. Malaria intensity indicators were calculated during the study period. Entomological evaluations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(85 citation statements)
references
References 35 publications
2
82
0
1
Order By: Relevance
“…(Nys. )albimanus) had the greatest density and biting activity between 18:30 and 19:30 hours, diminishing towards midnight as described in previous studies [26,32,44]. A study in Colombia also observed that the greatest intradomicile and peridomicile biting activity of An.…”
Section: Biting Activitysupporting
confidence: 70%
See 2 more Smart Citations
“…(Nys. )albimanus) had the greatest density and biting activity between 18:30 and 19:30 hours, diminishing towards midnight as described in previous studies [26,32,44]. A study in Colombia also observed that the greatest intradomicile and peridomicile biting activity of An.…”
Section: Biting Activitysupporting
confidence: 70%
“…To determine the human biting rate per night (HBR), the PHBC consisted in simultaneously having one person intradomicile and another in the peridomicile per night in the four households within each locality. Mosquito collections were conducted during the 18:00 and 22:00 hours, given that previous reports have indicated that this is the period of greater mosquito biting activity [32,33]. Collections were made during the rst 50 min of every hour.…”
Section: Collection Of Adult Mosquitoesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is clearly illustrated by guna communities, where a disproportionate number of malaria cases (> 90% in 2019) occurs despite representing a relatively small proportion (around 2.4%) of the whole population [13,18]. This crucial obstacle has been previously identi ed in several studies and reports from indigenous communities in Panamá [9,10,71,72], but remains a neglected issue to be solved. In this line, it is important to improve health services and reduced socioeconomical disparities in the indigenous reservations, precisely where malaria transmission persists [11,14].…”
Section: Association Between Malaria Incidence and Enso Eventsmentioning
confidence: 99%
“…More than one century has passed since the opening of the Panamá Canal and despite the increasing economic development observed in the country during the past decade [8], malaria continues to be a major public health concern particularly affecting socially marginalized populations. Nearly 90% of the malaria cases registered in the country during the past 40 years are from poor indigenous regions, and around 1000 annual cases have been reported for the last 15 years, mostly (~ 94%) by Plasmodium vivax [9][10][11][12]; re ecting the neglected status of this disease and marked health inequities associated with ethnicity in Panamá [10,11]. Indeed, the degree of socioeconomic inequity in Panamá reaches a value of 49.9 according to the Gini coe cient; one of the highest in Latin America [13].…”
Section: Introductionmentioning
confidence: 99%